A Sulfur Cathode with Pomegranate‐Like Cluster Structure. Issue 16 (8th May 2015) - Li, Weiyang; Liang, Zheng; Lu, Zhenda; Yao, Hongbin; Seh, Zhi Wei; Yan, Kai; Zheng, Guangyuan; Cui, Yi
<x xml:space="preserve">Abstract</x> A novel sulfur cathode with pomegranate‐like cluster structure is developed for high‐energy lithium–sulfur batteries. It has stable cycling stability, high volumetric energy density, and excellent rate capability.